Plasmid-mediated resistance to cephalosporins and quinolones in Escherichia coli from American crows in the USA - Jamborova, Ivana; Dolejska, Monika; Zurek, Ludek; Townsend, Andrea K; Clark, Anne B; Ellis, Julie C; Papousek, Ivo; Cizek, Alois; Literak, Ivan (Environmental microbiology, 2017)
American crow (Corvus brachyrhynchos) faeces were tested for Escherichia coli with plasmid-mediated quinolone resistance (PMQR), extended-spectrum beta-lactamases (ESBL) and AmpC beta-lactamases. A total of 590 faecal samples were collected at four roosting sites in the USA and cultivated on selective media. Pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST) were performed to assess clonality. Transferability of resistance genes was studied using conjugation and transformation bioassays. In total, 78 (13%, n = 590) cefotaxime-resistant isolates were obtained, of which 66 and 12 displayed AmpC and ESBL phenotypes, respectively. Fifty-four AmpC-producing isolates carried blaCMY-2 . Isolates producing ESBLs contained genes blaCTX-M-27 (5 isolates), blaCTX-M-15 (4), blaCTX-M-14 (2) and blaCTX-M-1 (1). Ninety isolates (15%, n = 590) with reduced susceptibility to ciprofloxacin were obtained, among which 14 harboured PMQR genes aac(6')-Ib-cr (4 isolates), qnrB19 (3), qnrS1 (2), qnrA1 (2), qnrB2 (1), qnrB6 (1) and qnrD3 (1). High genetic diversity was revealed by PFGE and MLST. Epidemiologically important E. coli clones (e.g., ST131, ST405) were identified. Plasmids carrying blaCMY-2 were assigned predominantly to IncA/C (8 plasmids), IncI1/ST23 (5) and IncI1/ST12 (3). The study demonstrates a widespread occurrence of E. coli with ESBL, AmpC and PMQR genes associated with clinically important multidrug-resistant clones and epidemic plasmids, in American crows.
Keywords: Multilocus Sequence Typing; Plasmids; cefotaxim; Bacterial Proteins; infekce vyvolané Escherichia coli; Electrophoresis, Gel, Pulsed-Field; vrány; antibakteriální látky; pulzní gelová elektroforéza; beta-Lactamases; Microbial Sensitivity Tests; Escherichia coli Infections; ciprofloxacin; Escherichia coli; beta-laktamasy; Ciprofloxacin; nemoci ptáků; proteiny z Escherichia coli; Animals; lidé; United States; Anti-Bacterial Agents; Escherichia coli Proteins; Cefotaxime; zvířata; Humans; mikrobiální testy citlivosti; Crows; Bird Diseases; bakteriální proteiny; multilokusová sekvenční typizace; plazmidy; Spojené státy americké